2013
DOI: 10.2169/internalmedicine.52.8390
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Feasibility and Efficacy of Autologous Stem Cell Transplantation in Elderly Patients with Multiple Myeloma

Abstract: Objective The feasibility and efficacy of high-dose melphalan (HD-MEL) followed by autologous hematopoietic stem cell transplantation (auto-SCT) in elderly patients with multiple myeloma (MM) are discussed. Methods We retrospectively analyzed and compared the results of 25 elderly patients (aged 65-76 years, elderly group) and 63 control patients (aged 51-64 years, control group). Many patients received a vincristine and doxorubicin combined with dexamethasone (VAD) regimen (elderly group: 92%, control group: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 27 publications
2
25
1
Order By: Relevance
“…1416 Nevertheless, some specific toxicities may occur with greater frequency among older patients with myeloma undergoing auto-HCT. For example, older adults may experience greater risk of cardiac toxicity (50% vs 10%; P <.0001), 17 arrhythmia (8% vs 0%; P =.02), 18 and oral/gastrointestinal toxicity (45% vs 23%; P =.06) 16 after auto-HCT. However, these age-related increases in toxicities have not been reported across all studies, and, in one report, older adults actually had less nausea than their younger counterparts (5% vs 18%; P =.007).…”
Section: Auto-hctmentioning
confidence: 99%
“…1416 Nevertheless, some specific toxicities may occur with greater frequency among older patients with myeloma undergoing auto-HCT. For example, older adults may experience greater risk of cardiac toxicity (50% vs 10%; P <.0001), 17 arrhythmia (8% vs 0%; P =.02), 18 and oral/gastrointestinal toxicity (45% vs 23%; P =.06) 16 after auto-HCT. However, these age-related increases in toxicities have not been reported across all studies, and, in one report, older adults actually had less nausea than their younger counterparts (5% vs 18%; P =.007).…”
Section: Auto-hctmentioning
confidence: 99%
“…Based on these reports, elderly patients with MM in otherwise fit medical condition have been considered to be eligible for ASCT irrespective of the chronological age in many institutions [21,22]. Accordingly, several single institution studies have reported their experience of ASCT in elderly patients [23][24][25][26][27][28][29][30]. As conditioning regimen before ASCT, reduced dosing of melphalan (100-140mg/m2) has been predominantly used in elderly patients, with no significant difference in transplant-related mortality and morbidity between elderly and younger patients.…”
Section: Introductionmentioning
confidence: 99%
“…7 However, many subsequent studies, mostly retrospective or registry-based and performed before the latest drugs became available, have shown encouraging results with ASCT in patients over 65 years of age. [8][9][10][11][12][13] Some investigators even reported a successful outcome for patients over the age of 70.…”
mentioning
confidence: 99%